Time in the stair-climbing test as a predictor of thoracotomy postoperative complications - Ambrozin, Alexandre Ricardo Pepe [UNESP]; Cataneo, Daniele Cristina [UNESP]; Arruda, Karine Aparecida [UNESP]; Cataneo, Antonio José Maria [UNESP] (Elsevier, 2013)
Objectives: The stair-climbing test as measured in meters or number of steps has been proposed to predict the risk of postoperative complications. The study objective was to determine whether the stair-climbing time can predict the risk of postoperative complications. Methods: Patients aged more than 18 years with a recommendation of thoracotomy for lung resection were included in the study. Spirometry was performed according to the criteria by the American Thoracic Society. The stair-climbing test was performed on shaded stairs with a total of 12.16 m in height, and the stair-climbing time in seconds elapsed during the climb of the total height was measured. The accuracy test was applied to obtain stair-climbing time predictive values, and the receiver operating characteristic curve was calculated. Variables were tested for association with postoperative cardiopulmonary complications using the Student t test for independent populations, the Mann-Whitney test, and the chi-square or Fisher exact test. Logistic regression analysis was performed. Results: Ninety-eight patients were evaluated. Of these, 27 showed postoperative complications. Differences were found between the groups for age and attributes obtained from the stair-climbing test. The cutoff point for stair-climbing time obtained from the receiver operating characteristic curve was 37.5 seconds. No differences were found between the groups for forced expiratory volume in 1 second. In the logistic regression, stair-climbing time was the only variable associated with postoperative complications, suggesting that the risk of postoperative complications increases with increased stair-climbing time. Conclusions: The only variable showing association with complications, according to multivariate analysis, was stair-climbing time. © 2013 by The American Association for Thoracic Surgery.
Keywords: adult; exercise test; female; Fisher exact test; forced expiratory volume; human; logistic regression analysis; lung resection; major clinical study; male; postoperative complication; predictive value; priority journal; rank sum test; receiver operating characteristic; spirometry; stair climbing test; Student t test; thoracotomy; time; Exercise Test; Female; Humans; Male; Middle Aged; Postoperative Complications; Predictive Value of Tests; Thoracotomy; Time Factors